Structure–Antimicrobial Activity Relationships of Recombinant Host Defense Peptides Against Drug-Resistant Bacteria - Travé Asensio, Sergio (2025)
Host defense peptides (HDPs) represent a valuable class of antimicrobial agents with the potential to address the growing threat of antimicrobial resistance (AMR). Here, we have studied recombinant constructs based on combination of HDPs fused to the GFP protein and multidomain proteins combining three or four HDPs in a single polypeptide, referred as 1st and 2nd generation antimicrobials, respectively. These recombinant peptides were tested against Gram-positive and Gram-negative bacteria associated in healthcare infections. In addition, in silico studies provided insight into the antimicrobial structure-activity relationships of these biomolecules. For the 1st generation of antimicrobials, amphipathicity mainly explains the average antimicrobial activity against the Gram-positive strains. In the case of the Gram-negative bacteria, it depends on the quantity and the exposed area of the Ser and Thr amino acids. For the 2nd generation of antimicrobials, the order of domains is crucial to act against Gram-positive strains, preferably by positioning the most bioactive domain against the Gram-positive pathogen at the ends.